Comparison of different food consumption methods to digital food photography method of elderly in nursing home - Orkun Erkılıç, Tuğçe; Rakıcıoğlu, Neslişah (Progress in Nutrition, 2020)
Background: Detection of food consumption by digital photography is a recently applied method in the world. The main purpose of the present study was to identify the most efficient method in determining the food consumption of the elderly in the nursing home by comparing different food consumption records to the digital photography method. Methods: A total of 52 (27 men, 25 women) elders, who did not have a neurological or psychiatric disturbance, were included in the study. The study was carried out in Ankara Seyranbağları Nursing Home Directorate for the Elderly Care and Rehabilitation Center. Nutritional status was screened using a questionnaire from the Mini-Nutritional Assessment, basic characteristics were determined and anthropometric measurements were assessed. Food consumption of elderly people was evaluated by daily food record, 24 hour retrospective food record, food frequency, and digital photography method, and the relevancy of these methods for the elderly were evaluated. Results: Most of the consumed food groups (milk, yoghurt, cheese, red meat, potatoes, fruit, oil, and sugar group for elderly men, eggs, red meat, fish, meat products, legume, bread, cereals, other vegetables and fat group for elderly women) were found to be highest according to food frequency, and then food records and lowest mean values were obtained by digital photography. At the end of the research, when the mean consumption of energy, protein, fat, and carbohydrate of elderly were ordered in descending order, it was seen that for all genders the order was same: the highest means had seen on food records than food frequency and the lowest means had seen on digital photography. Conclusions: As a result, the digital photography method can record the full food consumption of the elderly in the nursing home and it is also a promising method.